The Euro, Inflation and Consumer$1 (Bs Perceptionss Lessons from Italy - Giovane, Paolo Del.; Sabbatini, Roberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
On 1 January 2002, euro banknotes and coins were introduced in twelve EU Member States. Three more countries joined in the following years, and over 300 million people now use the euro in their daily transactions. The currency changeover was a technical success. From the very start, however, the vast majority of euro area citizens held the single currency responsible for a sharp rise in prices and a subsequent decline in their personal economic fortunes. This book puts forward convincing empirical evidence, primarily drawn from Italy$1 (Bs experience, to establish whether the introduction of the euro has had a major impact on prices, and if not, why so many people believe it has. Its significance lies not only in the documentation of a historic event, but also and more importantly, in the lessons it provides, which concern the public$1 (Bs understanding of inflation, the correct assessment of the effects of the single currency, and the need for appropriate measures when other countries adopt the euro.s
Perceived and measured inflation after the launch of the euro: explaining the gap in Italy -- Rounding and (3z(Banomalous(3y (Bchanges in Italian consumer prices in 2002 -- Pricing behaviour and the introduction of the euro: evidence from a panel of restaurants -- Did prices really soar after the euro cash changeover? Evidence from ATM withdrawals -- Memory for prices and the euro cash changeover: an analysis for cinema prices in Italy -- What$1 (Bs behind (3z(Binflation perceptions(3y(B? A survey-based analysis of Italian consumers -- Impact of the cash changeover on prices and inflation perceptions in the euro area: a survey of the empirical evidence.s
Keywords: Macroeconomics; European Economic Community literature; Economics; Macroeconomics/Monetary Economics//Financial Economics; European Integration; Electronic books